"Business Crimes" in Entertainment and Sports:A Primer and Discussion in the Subtext of the Olympics and International Sports - Hunter, Jr., Richard J.; Shannon, John H.; Lozada, Héctor R. (Archives of Business Research, 2017)
An important area of law involves crimes committed in the business environment. Part I of this article is a discussion of “business property crimes,” such as larceny, burglary, robbery, and others. Part II then introduces the category of offenses termed "White-Collar Crimes.” The authors provide examples in the context of sports and entertainment, which intersect in the cases of O. J. Simpson and Norby Walters. Part III offers a discussion on international implications emanating from enforcement actions relating to corruption and bribery under the Foreign Corrupt Practices Act (FCPA) in the context of the Olympic Games and other international sporting events. The authors propose a revision of the FCPA, “The Olympic Bribery Act,” to remedy deficiencies in the current statutory framework.